THEORETICAL ASPECTS OF REGULATION OF ENVIRONMENTALLY SAFE PRODUCTION OF AGRICULTURAL PRODUCTS - RATOSHNIUK, Tatiana; SOKOLOVA, Alla; RATOSHNIUK, Viktor; MARTYNYUK, Mykhailo (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The socio-economic development of Ukraine requires increasing the level of food security of the state, providing the population with high-quality and ecologically safe food products in order to preserve their health and improve the welfare of society. The safety of food for the health of the population can be guaranteed only under the condition of organizing strict quality control of food products entering the domestic market, as well as through the implementation of a stimulating policy for the production of ecological products. In this connection, there is an objective need to develop and introduce a set of coordinated organizational and economic measures, which should be based on stricter public, state and self-government control over compliance with established norms and standards regarding production technologies and be implemented at all stages of the product life cycle. An important role in this context will be played by increasing the social responsibility of business, popularization of environmentally safe and energy-saving technologies, greening of all production and consumption processes, which requires coordinated cooperation of managers, managers and employees of agricultural, agro-industrial and processing enterprises, scientists, educators and the public.The legal regulation of the agro-industrial complex of Ukraine has the greatest influence on the regulation of ecologically safe production of agricultural products. Ecological safety of agricultural products is the state of agricultural products, in which the state has established and established in current legislation mandatory safety parameters for this type of products, special sanitary and veterinary measures and requirements for both products and their producers, establishment of uniform standards safety, uniform systems of certification and marking, state control and supervision of the fulfillment of requirements and standards of environmental safety in the production and sale of agricultural products, as well as establishing norms of administrative, criminal, and civil liability for their violation. The main goals of state regulation of the agricultural sector are: guaranteeing the food security of the state; providing the population with quality food products; providing industry with raw materials; solving the problems of the economic and social nature of the development of the agricultural industry; ensuring the investment attractiveness of the agricultural sector; increasing the export potential of the agricultural sector.
Keywords: environmentally safe production; product quality; state regulation; food safety